The parturition-relevant hormone profile in hyper-prolific sows under different housing conditions - Lehn, Desirée; Blim, Sarah; Oster, Michael; Otten, Winfried; Failing, Klaus; Scheu, Theresa; Koch, Christian; Thaller, Georg; Teifke, Jens Peter; Bostedt, Hartwig (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2025)
Aim was to characterize birth-relevant hormone profiles of reproductively productive hybrid sows in the peripartum period. It was examined whether there are deviations in the hormone profile depending on the birth process (eutocia:dystocia) and the type of housing (box stall BS vs. farrowing pen FP vs. group housing GH).A total of 40 healthy, heavily pregnant hybrid sows (German Landrace x Large White) with a gestation number≥ 2 were available. The distribution between the housing types was: BS n=18, FP n=15, GH n=7. All births occurred after the biologically completed gestation period. Blood samples were taken via indwelling catheters (113th day ante partum to 4th day post partum). Progesterone (P4), oestradiol (E2), prostaglandin F2α and its metabolites (PGFM), relaxin, oxytocin, cortisol, adrenaline and noradrenaline were determined.The ratio of eutocia:dystocia was 15:25. Dystocia occurred regardless of type of housing. The only reason for dystocia was a weak labor (>60 min). The litter size was 17.73± 3.85 piglets. Differences in the hormone profiles between eutocia and dystocia were as follows: P4 tended to be higher in dystocia p=0.0776; oxytocin higher in eutocia (not significant), 12.5% of sows permanently with hypoxytocinemia; cortisol p=0.0503; noradrenaline p=0.0098. The type of housing had the following influence on the hormone profile: P4 p=0.046; E2 p=0.0009; PGFM p=0.0108; relaxin p=0.0022; noradrenaline p=0.0078.The parturition-relevant hormones are related to the parturition and to the type of housing during birth. The hormone profiles obtained could be of use in the discussion about the animal welfare-oriented housing system in the peripartum phase in pigs. The proportion of sows of the hyperproliferative line studied with permanent hypoxytocinaemia in stage II of parturition is remarkable. The ratio of eutocia:dystocia is unevenly distributed. Dystocia occurred regardless of the type of housing.
Keywords: Birth; dystocia; farrowing crate; farrowing pen; hormone; parturition; prolific sows